Analysis of Determinant Factors of The Bed Occupancy Rate of Ar-Rahman and Al-Ikhlas Inpatients at IBNU SINA YW UMI Hospital, 2023 - Mutiara, Mutiara; Nurelly, Nurelly; Ningsi, Iin Widya; Murfat, Zulfitriani; Zulfahmidah, Zulfahmidah (Jurnal Biologi Tropis, 2024)
Hospitals are required to provide the best and highest quality services so that more and more patients will be comfortable and satisfied when going to the hospital for treatment. This study aims to analyze the determinants of the BOR value of Ibnu Sina YW UMI Hospital. The type of research is quantitative research, descriptive analysis using a cross sectional method, and the research sample was 27 people. Data were analyzed using univariate analysis to describe the characteristics of each research variable. The research results found that the BOR (Bed Occupancy Rate) value for Ar-Rahman and Al-Ikhlas inpatient care at Ibnu Sina YW UMI Hospital was efficient according to standards. The hospital service that influences the inpatient BOR value is satisfaction with the nutritional food menu provided. Hospital facilities that influence inpatient BOR values are satisfaction with radiology facilities. The general perception of patients that influences the inpatient BOR value is a feeling of great satisfaction with fast service. It is hoped that this research can help determine the factors determining the Bed Occupancy Rate (BOR) value of Ar-Rahman and Al-Ikhlas Inpatients at Ibnu Sina YW UMI Hospital.